A randomized controlled open label comparative clinical study of cephalexin versus doxycycline in patients with acne vulgaris in a hospital based population of South India - Banerjee, Prithwijt; Maity, Somnath; Bubna, Aditya; Das, Manisha (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Oral antibiotics are frequently used for acne vulgaris. Cephalexin has documented some success against acne vulgaris in earlier studies. Here the efficacy and safety of Cephalexin have been compared against the standard therapy of Doxycyline. Methods: From September 2010 to June 2011, 100 patients of moderate Acne vulgaris were randomized into two groups to receive oral Doxycyline (100mg once daily) or Cephalexin (500mg thrice daily) in an open label manner for eight weeks. All participants were allowed to use topical 5%Benzoyl peroxide gel twice daily. Efficacy was measured in terms of reduction in the number of facial comedones and inflammatory lesions from baseline after eight weeks. Results: 44 patients from Cephalexin group and48 patients from Doxycyline group completed the study. Both drugs have significantly decreased comedone count as well as the inflammatory lesion count after eight weeks. However, Doxycycline appeared better in terms of Comedone count (14.5±3.07 versus 12.9±4.31, p=0.045) as well as inflammatory lesion count (8.64.1±2.14 versus 7.67±2.46, p=0.047) at the end. The total adverse event was slightly more with Cephalexin (6.81% versus 6.25%, p= 0.912), where Diarrhoea remained the commonest adverse effect (4.54%). Conclusions: Although for the first time oral Cephalexin has displayed efficacy against moderate acne vulgaris in a prospective clinical study, it appeared inferior to Doxycycline over eight weeks. Therefore, it becomes an option only when other oral antibiotics are contraindicated or not tolerated.